Cancer Immunotherapy and the Immune Response in Follicular Lymphoma - Stenner, Frank; Renner, Christoph (Frontiers in Oncology, 2018)
Follicular lymphoma (FL) is the most frequent indolent lymphoma in the Western world and is characterized in almost all cases by the t(14;18) translocation that results in overexpression of BCL2, an anti-apoptotic protein. The entity includes a spectrum of subentities that differ from an indolent to a very aggressive growth pattern. As a consequence, treatment can include watch & wait up to intensive chemotherapy including allogeneic stem cell transplantation. The immune cell microenvironment has been recognized as a major driver of outcome of FL patients and gene expression profiling has identified a clinically relevant gene expression signature that classifies an immune response to the lymphoma cells. It is known for some time that the immune cell composition of the lymphoma microenvironment is important because high numbers of tissue-infiltrating macrophages correlate with poor outcome in patients receiving chemotherapy but not in patients receiving the combination of chemotherapy and CD20-specific monoclonal antibody rituximab. In addition, TCR signaling of tumor-infiltrating lymphocytes is dysfunctional leading to an impaired capacity to form an intact immunologic synapse. Approaches restoring local T cell function, e.g., by usage of checkpoint inhibitors has demonstrated clinical activity (ORR 40%) and can achieve long-term remissions. Ongoing trials with re-programmed autologous CART cells achieve response rates in approximately 50% of FL patients with relapsed and even refractory disease. Responses lasting for more than 6 months might be durable, indicative for a successful restoration of a functional immune system. In summary, FL is a malignant disease where the control by the immune system ultimately decides about progression and transformation rate. The advent of monoclonal antibodies has changed the way we treat FL and new approaches restoring the individual immune control will hopefully improve results further.